Synchronization of chaotic dynamical systems: a brief review - Laureano, M. (2017)
There are several reasons for the approach to chaos synchronization. This phenomenon is immediately interesting because of its high potential for applications. But, first of all, it is particularly interesting the study of a phenomenon that requires the adjustment of dynamic behaviors in order to obtain a coincident chaotic motion, being this possible even in chaotic dynamical systems in which sensitive dependence on initial conditions is one of the features. The possibility of applying techniques of chaos control in order to optimize the results of synchronization is alsoa motivating factor for the study of this phenomenon. It is presented a brief review of preliminary notions on nonlinear dynamics and then is considered in detail the synchronization of chaotic dynamical systems, both in continuous and discrete time.